2019
DOI: 10.1016/j.scitotenv.2018.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater alters feeding rate but not vitellogenin level of Gammarus fossarum (Amphipoda)

Abstract: This study was conducted in accordance with national and institutional guidelines for the protection of human subjects and animal welfare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…VTG secretion, unique to female sh species, has been widely used in different studies as a marker of feminisation in different male sh species due to estrogenic inuence of contaminants in water bodies. 78,85,[125][126][127][128][129][130][131][132][133] Assessment of VTG expression is oen used in conjunction with other estrogenicity bioassays as a complementary method for assessment of endocrine disruption within aquatic fauna. Such application was employed by Geraudie et al (2017) and Ganser et al (2019) in their studies where YES assay was used to evaluate estogenicity of water samples in addition to the VTG assay.…”
Section: Detected Estrogenic Activity In All Matricesmentioning
confidence: 99%
See 3 more Smart Citations
“…VTG secretion, unique to female sh species, has been widely used in different studies as a marker of feminisation in different male sh species due to estrogenic inuence of contaminants in water bodies. 78,85,[125][126][127][128][129][130][131][132][133] Assessment of VTG expression is oen used in conjunction with other estrogenicity bioassays as a complementary method for assessment of endocrine disruption within aquatic fauna. Such application was employed by Geraudie et al (2017) and Ganser et al (2019) in their studies where YES assay was used to evaluate estogenicity of water samples in addition to the VTG assay.…”
Section: Detected Estrogenic Activity In All Matricesmentioning
confidence: 99%
“…78,85,[125][126][127][128][129][130][131][132][133] Assessment of VTG expression is oen used in conjunction with other estrogenicity bioassays as a complementary method for assessment of endocrine disruption within aquatic fauna. Such application was employed by Geraudie et al (2017) and Ganser et al (2019) in their studies where YES assay was used to evaluate estogenicity of water samples in addition to the VTG assay. 85,133 Unexpectedly, while Ganser et al 85 found signicant induction of estrogenic signals from the YES assay, VTG level was not signicantly induced in the male shes sampled.…”
Section: Detected Estrogenic Activity In All Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ganser et al. (2019) reported no change in vitellogenin levels of G. fossarum when exposed to WW, but only males were tested. The potential for reduced fecundity in response to chemical pollution indicated by our study may have population‐level consequences (Hoffmann & Hercus, 2000), yet this endpoint is rarely used in ecotoxicological studies.…”
Section: Discussionmentioning
confidence: 99%